Clinical and laboratorial aspects related to juvenile recurrent parotitis - Fernandes, Darcy; Nogueira, Vinicius Krieger Costa; Silveira, Heitor Albergoni; León, Jorge Esquiche; Domingues, Natalia Bertolo; Giro, Elisa Maria Aparecida; Bufalino, Andreia (Journal of Oral Diagnosis, 2021)
Juvenile Recurrent Parotitis (JRP) is an inflammatory condition characterized by recurrent parotid gland inflammation episodes of non-suppurative and non-obstructive nature. This is the second most common salivary disorder in childhood. We present a case of a 5-year- old girl with a recurrent facial swelling on the left side. Panoramic x-ray image excluded any dental or osseous involvement, as well as the presence of sialoliths. Ultrasonography showed hyperechoic focal areas with cavitation of the parotid gland corresponding to sialectasis. Sorological tests for infections like HIV, cytomegalovirus, mumps and other chronic diseases were negative. Based on the clinical and laboratorial features, the diagnosis was compatible with JRP. After two months of follow-up, the patient returned without any swelling or symptomatology. Seven months later, the patient returned with a new facial swelling episode, and this time on the right side. Clinicians should be aware of this condition and include in the differential diagnosis of salivary gland diseases of pediatric patients.